Manajemen Kurikulum Terpadu Di SMPIT Luqmanul Hakim Bandung - Nur Ahmad (Jurnal Pendidikan Islam Indonesia, 2019)
The integrated Islamic curriculum as one of the educational programs has a strategic role in forming, building, fostering and directing students to become good people who have positive character and personality, self-understanding, skilled and teamwork.This research aims to obtain documents related to the management of planning, implementation, evaluation of integrated curriculum at SMPIT Luqmanul Hakim Bandung. The method used in this research is descriptive analytic method with a qualitative approach. The data obtained by using interview, observation and documentation study. The finding of this research are first, planning for integrated Islamic curriculum carried out by compiling the curriculum, formulating for lesson planpreparation by put in the characteristics of an integrated Islamic curriculum. Second, the implementation of an integrated Islamic curriculum refers to planning that has formulated by put in the verses of the Qur’an in the lesson plan. Third, evaluation is carried out in order to know the success of students.